TANTANGAN AUDITOR INTERN MENGHADAPI GLOBALISASI - Imas Tita Rosita (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2016)
In the context of globalization of business operations, development of information technologies, complexity of business transactions, and business risk, internal Auditors are burdened a lot of tasks in which they should involve seriously. Auditors face the challenges of reconciling their need to make a meaningful contribution to the business with the meeting the needs of their customers, audit committee, executive management, and line management. Conflicts are occurred due to lack of communication between auditors and their customers. In this case, director of audit director has a important role to overcome it as soon as possible. The director is required to have good communications skills, personal confidence in dealing effectively with conflicts at the executive or board level.